High genome diversity of Klebsiella pneumoniae strains isolated from a Chinese traditional medicine hospital in Jiangsu province, China, from 2023 to 2024 - Wang, Yitong; Qin, Si; Guo, Hongxiong (Frontiers in Microbiology, 2025)
ObjectiveKlebsiella pneumoniae (KP) poses a global health threat, with variations observed across different regions. However, data on the genomic characteristics and drug resistance profiles of KP isolates in Eastern China are limited. To address this gap, we collected KP isolates from a traditional Chinese medicine hospital in Jiangsu Province, China, in order to characterize these features.MethodsFrom February 2023 to February 2024, 117 KP isolates were collected from a Chinese traditional medicine hospital in Jiangsu province, China. Antimicrobial susceptibility testing and whole-genome sequencing were performed on all isolates. Then, capsular serotype, multi-locus sequence typing, virulence genes, and resistance genes were identified using Prokka and Kleborate software tools. The hypermucoviscosity phenotype was detected using the string test. Antimicrobial susceptibility was tested following the guidelines by the Clinical and Laboratory Standards Institute, using a commercially prepared and dehydrated panel. A chi-squared test was performed to assess the differences in virulence gene profiles between hypermucoviscous and non-hypermucoviscous isolates.ResultsA high resistance rate to ampicillin (98.7%) and doxycycline (41.0%) was observed in the KP strains. The resistance rate to cephalosporins ranged from 10 to 20%, and 23.7% of the strains were multidrug-resistant (MDR). A total of 66 resistance genes from 13 categories were identified, including carbapenem-resistant genes in four KP strains. The most common capsular serotypes were K1 and K2 (24.0% of the isolates). O1 was the dominant O antigen type (52.1%). The KP strains were classified into 62 sequence types (STs), with ST23, ST29, ST412, and ST111 being the most prevalent (each accounting for >5.0% of the isolates). The carriage rates of the virulence genes aerobactin, yersiniabactin, colibactin, salmochelin, RmpADC, and RmpA2 were 44.4, 47.9, 11.1, 54.7, 55.6, and 31.6%, respectively. All ST23 KP strains carried virulence plasmids other than RmpADC. Hypermucoviscous (HM) KP was observed in 23.4% of the isolates. HM KP strains carried a higher number of virulence genes compared to the non-HM KP strains.ConclusionAlthough no single dominant (KP) clone, serotype, or sequence type was identified among the isolated KP strains from this hospital, the overall resistance rates remained relatively low. However, the relatively prevalent ST23 KP strains, which carry multiple virulence genes, are a concern due to their potential to acquire carbapenem-resistant genes.